Synthetic Approaches towards the Sulfonamide Substituted‐1, 5‐Diarylimidazole‐2‐thiones as Selective Cyclooxygense‐2 inhibitors. (8th October 2013) - Navidpour, Latifeh; Amini, Mohsen; Miri, Ramin; Firuzi, Omidreza; Tavakkoli, Marjan; Shafiee, Abbas
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>